PERAN ASEAN COMMISSION ON THE PROMOTION AND PROTECTION OF THE RIGHTS WOMEN AND CHILDREN (ACWC) DALAM MENANGGULANGI WOMEN TRAFFICKING DI INDONESIA TAHUN 2018-2020 - Amaria, Cheryl Puspa; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is done focusing on the role of ACWC in Indonesia on combatting trafficking of women in 2018-2020. ACWC is a regional corporation under ASEAN, focusing on the protection of women’s and children’s rights, including all transnational women protection activities im ASEAN’s member states. Thiss reserach is aiming to understand the role of one group to another group.            This research is done by using international organisation theory, group analysis level to understand the influence of a group on certain issue. The datas are collected by using qualitative methodology, collecting datas by using library research method, most of the datas are published by ACWC official website, ASEAN official website, journals and books that talking abut women trafficking in Indonesia.The result of this research showed that ACWC contibuting in helping Indonesia on combatting women trafficking is done by many ways, through assisting law that is needed in Indonesia, National Action Plan, establishing law corporation in national level,  providing support in medical and law capacity, improving public awareness by doing gender mainstreaming in programmes and social champagne in public.  Key Words: ACWC, Indonesia, Women Trafficking, ASEAN, Sexual Exploitation